The Social Services : The immediate problem and the way forward (London : The Socialist Medical Assocation)
1944 1944 1940s 34 pages problems which he must face in his capacity as a producer. As specialists we look forward to a social system in which industry shall be run to meet the needs of people, instead of people being mainly organised to meet the needs of industry. But even while working to achieve this aim the workers can, through their organisations obtain better conditions and indeed the whole history of the labour movement demonstrates the struggle for this alongside the demand for better wages. During the war great advances have been made as regards industrial welfare and the Trade Union organisations have been able to insist with the help of a Labour Minister, that wartime legislation designed for maximum production such as the Essential Work Order has also incorporated certain minimum requirements in respect of welfare facilities. Though the short-sightedness of some government departments, and the reactionary attitude of some employers have held up progress in this direction, the development of welfare departments in factories has certainly received a stimulus from the war, and what is perhaps most important, workers organisations have taken part in and often initiated, drives to improve conditions, and have done this in a new way. In pre-war days if conditions were bad, the workers had recourse to mere demands for improvement, backed by threats 25 15X/2/464/1